2004
DOI: 10.1007/s00394-004-0528-5
|View full text |Cite
|
Sign up to set email alerts
|

n–3 polyunsaturated fatty acids supplementation decreases asymmetric dimethyl arginine and arachidonate accumulation in aging spontaneously hypertensive rats

Abstract: EPA and DHA supplementation reduced ADMA accumulation in SHR in parallel with a decrease of arachidonate availability. This finding suggests that the control of the inflammatory ground of endothelium might play an important role in EPA and DHA effect on this novel and highly predictive cardiovascular risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…21 It is possible that EPA's ADMA reduction effect may have been particularly emphasized in our study, because each of the subject patients had backgrounds of cerebral infarction, many of which were accompanied by hypertension and DM. Moreover, in the study in which EPA was administered to spontaneously hypertensive rats, the reduction in the level of ADMA was greater in the EPA-administered group than it was in the group that was administered olive oil, 22 supporting the fact that EPA reduces ADMA.…”
Section: Discussionmentioning
confidence: 92%
“…21 It is possible that EPA's ADMA reduction effect may have been particularly emphasized in our study, because each of the subject patients had backgrounds of cerebral infarction, many of which were accompanied by hypertension and DM. Moreover, in the study in which EPA was administered to spontaneously hypertensive rats, the reduction in the level of ADMA was greater in the EPA-administered group than it was in the group that was administered olive oil, 22 supporting the fact that EPA reduces ADMA.…”
Section: Discussionmentioning
confidence: 92%
“…Plasma levels of ADMA are significantly higher in SHRs at 4 weeks (prehypertensive stage), 12 weeks (hypertensive stage), and 24 weeks (hypertensive endorgan damage stage) [34] . A significantly higher concentration of plasma ADMA also exists in aging (16-month-old) male SHRs [38] . These findings indicate that a reduced NO bioavailability is associated with hypertension and end-organ damage [36] and that ADMA is a risk factor for ED [38] .…”
Section: Similar Pathogenesis Of Ed and Asymmetric Dimethylarginine Imentioning
confidence: 97%
“…A significantly higher concentration of plasma ADMA also exists in aging (16-month-old) male SHRs [38] . These findings indicate that a reduced NO bioavailability is associated with hypertension and end-organ damage [36] and that ADMA is a risk factor for ED [38] . The information obtained from SHRs suggests a low bioavailability of NO and impairment of the L -arginine-NO pathway in humans [23] .…”
Section: Similar Pathogenesis Of Ed and Asymmetric Dimethylarginine Imentioning
confidence: 97%
“…24) It has been well reported that a 20:4n-6 decline would be caused by 22:6n-3 administration in vivo. [25][26][27][28] In the present study, the hepatic 20:4n-6 decline in newborn rats resulted from indirect diet intervention by supplementing the experimental diets fed to the dams. The D6D mRNA expression level showed that D6D was significantly low in the newborn pups fed by the dams that had received the DHA diet, which may account for the decline of 20:4n-6 in the newborn liver.…”
Section: Discussionmentioning
confidence: 99%